Caribbean Report 18-01-1989 - Timmins, Jerry (anchor); Tomlinson, Alan (correspondent); Mitchell, James (interviewee); Daly, Margaret (interviewee); Whitehorne, Pat (correspondent); Johnson, Martin (correspondent) (The British Broadcasting Corporation, 1989)
In Jamaica, campaigning for the February 9th, general elections is in full swing with both parties staging meetings and motorcades throughout the island nation. As President-elect George Bush takes up the reigns of power in the United States, all eyes are on him in the Caribbean to see what changes he plans in foreign policy. Prime Minister of St. Vincent and the Grenadines, James Mitchell speaks for greater opportunities in education and higher aid allocations. With the planned EEC/ACP meeting in Barbados, Margaret Daly, British Conservative Member of the European Parliament intends to raise a motion for continued preferential treatment for bananas in the Caribbean. England's Test and Cricket County Board meets tomorrow in London ahead of next week's ICC meetings. England is expected to agree to a compromise over the issue of South Africa and agree to the West Indies latest resolution which enforces punitive measures for players after April 1st.
1. Headlines (00:00-01:08)
2. In Jamaica, campaigning for the February 9th general elections is in full swing with both parties staging meetings and motorcades throughout the island (01:09-05:28)
3. As President-Elect George Bush takes up the reigns of power in the United States, all eyes are on him in the Caribbean to see what he plans in foreign policy. Prime Minister of St. Vincent and the Grenadines, James Mitchell spaeks on opportunities in education and higher aid allocations (05:28-08:05)
4. Financial News (08:05-09:45)
Keywords: Elections -- Jamaica.; Economic assistance - Caribbean Area.; Education -- Caribbean Area.; Cricket players -- United Kingdom.; Cricket.; Apartheid.; Apartheid -- South Africa.; People's National Party -- Jamaica.; ACP; EEC